2016
DOI: 10.1158/2159-8290.cd-16-0745
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of the Noncoding Cancer Genome: A Target of Genetic and Epigenetic Alterations

Abstract: The emergence of whole-genome annotation approaches is paving the way for the comprehensive annotation of the human genome across diverse cell and tissue-types exposed to various environmental conditions. This has already unmasked the positions of thousands of functional cis-regulatory elements integral to transcriptional regulation, such as enhancers, promoters and anchors of chromatin interactions that populate the noncoding genome. Recent studies showed that cis-regulatory elements are commonly the targets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 200 publications
2
59
0
1
Order By: Relevance
“…Previous studies have shown that tumors exhibit both genetic and epigenetic heterogeneity within cell populations, and that epigenetic changes, such as DNA methylation and/or histone modifications, accumulate in the genome throughout oncogenesis (12)(13)(14)(15). This dynamic landscape may permit the introduction of adaptive ALK-independent mechanisms of drug resistance within targeted cells.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that tumors exhibit both genetic and epigenetic heterogeneity within cell populations, and that epigenetic changes, such as DNA methylation and/or histone modifications, accumulate in the genome throughout oncogenesis (12)(13)(14)(15). This dynamic landscape may permit the introduction of adaptive ALK-independent mechanisms of drug resistance within targeted cells.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, mutations occurring in cis‐regulatory elements (i.e., enhancers and promoters) are of particular interest, as they can directly alter expression of associated gene products, by directly or indirectly altering DNA binding of TFs (Deplancke et al, ; Shi et al, ). Such mutations are frequent in breast cancer (Bailey et al, ; Zhou et al, ; Rheinbay et al, ; Gyorffy et al, ), but their significance is generally unclear (Nik‐Zainal et al, ). However, mutations in ESR1 enhancer sequences found in ~ 7% of breast cancers have now been shown to be responsible for altering ESR1 expression by modulating TF binding activity (Bailey et al, ).…”
Section: Altered Transcriptional Regulation In Human Breast Cancersmentioning
confidence: 99%
“…Data are drawn from the 993 breast cancer cases in the TCGA PanCancer Atlas study analyzed and plotted via cBioportal (http://www.cbioportal.org). (Bailey et al, 2016;Zhou et al, 2016;Rheinbay et al, 2017;Gyorffy et al, 2018), but their significance is generally unclear (Nik-Zainal et al, 2016). However, mutations in ESR1 enhancer sequences found in~7% of breast cancers have now been shown to be responsible for altering ESR1 expression by modulating TF binding activity (Bailey et al, 2016).…”
Section: Ube2tmentioning
confidence: 99%
“…In the past decades, lots of ncRNAs have been found, such as ribosomal RNA (rRNA), transfer RNA (tRNA), small nuclear RNA (snRNA) and microRNA (miRNA) as well as long non‐coding RNA (lncRNA). Aberrations within the non‐coding genome are major decisive factors contributed to human diseases . Among these non‐protein‐coding transcripts, lncRNAs, defined as longer than 200 nucleotides with little or no protein‐coding ability, have emerged as essential regulators in diverse biological processes .…”
Section: Introductionmentioning
confidence: 99%